2018
DOI: 10.12659/msm.910930
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Increases Cardiac Rupture After Myocardial Infarction via the AMPK-MTOR/PGC-1α Signaling Pathway in Rats with Acute Myocardial Infarction

Abstract: BackgroundCardiac rupture often occurs after acute myocardial infarction due to complex and unclear pathogenesis. This study investigated whether metformin increases the incidence of cardiac rupture after myocardial infarction through the AMPK-MTOR/PGC-1α signaling pathway.Material/MethodsAn acute myocardial infarction (MI) mouse model was established. A series of experiments involving RT-qPCR, Western blot, TUNEL staining, and Masson staining were performed in this study.ResultsMyocardial infarction occurred,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…In critically ill patients there is a risk of hypoglycaemia-related morbidity associated with intensive glucose control with intravenous insulin [41, 42], although we did not have data on acute glucose control in our study. In pre-clinical studies, increased myocardial rupture after AMI has been observed with metformin, which has been attributed to increased AMPK-MTOR/PGC-1α-mediated cardiomyocyte autophagy, but we were unable to assess this [43].…”
Section: Discussionmentioning
confidence: 99%
“…In critically ill patients there is a risk of hypoglycaemia-related morbidity associated with intensive glucose control with intravenous insulin [41, 42], although we did not have data on acute glucose control in our study. In pre-clinical studies, increased myocardial rupture after AMI has been observed with metformin, which has been attributed to increased AMPK-MTOR/PGC-1α-mediated cardiomyocyte autophagy, but we were unable to assess this [43].…”
Section: Discussionmentioning
confidence: 99%
“…Metformin has been demonstrated to activate the phosphorylation of AMPK in cardiomyocytes and mouse cardiac tissues. In fact, a recent study suggested that short-term treatment with metformin protects against myocardial ischemia-reperfusion injury via the AMPK signaling pathway after myocardial infarction in mice (Hua et al, 2018). Therefore, AMPK has been considered to have various cardioprotective effects in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…Adenosine 5’-monophosphate-activated protein kinase (AMPK) is an essential metabolic regulator for energy sensing and has been well documented (Toyama et al, 2016); AMPK is expressed specifically in various tissues and cells, including cardiomyocytes (Hua et al, 2018), and plays a crucial role in regulating energy metabolism and energy homeostasis under stress conditions. AMPK can be activated by various conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4A,B). KEGG pathway analysis showed that the differentially expressed mRNAs were mostly enriched in viral myocarditis, the mTOR signalling pathway 24 , circadian rhythm, arrhythmogenic right ventricular cardiomyopathy (ARVC), and the metabolism pathway 25 (Fig. 4C,D).…”
Section: Functional Analysis Of Differentially Expressed Genes In Pbmmentioning
confidence: 99%